(untitled) (Ustozlar uchun, 2025)
Delaying important tasks, known as procrastination. It is a widespread challenge among both students and professionals. This articleinvestigates the psychological and behavioral factors that cause procrastination and presents practical strategies to manage time more effectively. A review of recent research shows that low self-regulation, task aversion, lack of confidence, and poor time-management skills play a significant role. Strategies such as breaking tasks into smaller parts, implementing SMART goals, using the Pomodoro technique, prioritizing tasks, limiting distractions, and fostering self-leadership have been found to be effective. Consistent application of these methods can improve productivity, increase focus, reduce stress, and support better academic performance.